2012
DOI: 10.1080/00981389.2012.714847
|View full text |Cite
|
Sign up to set email alerts
|

To Live Close to a Person With Cancer—Experiences of Family Caregivers

Abstract: The purpose of this study was to obtain a deeper understanding of the experiences of Family Caregivers (FC) living close to a patient with cancer. This article reports on the findings from individual interviews with 15 FCs of patients with cancer. The interview transcripts were analyzed using qualitative hermeneutic analysis. This study revealed that living close to a cancer patient over the course of his or her illness affected many aspects of FCs lives in significant ways. Their experiences can be summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Being overwhelmed and having trouble finding time for oneself has been highlighted in previous quantitative and qualitative research with caregivers (Carlander et al, 2011;Stenberg et al, 2012). Throughout the interviews, most of the caregivers referred to their caregiving experience prior to starting the exercise programme as overwhelming, wherein they struggled to cope and find time for their own self-care.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Being overwhelmed and having trouble finding time for oneself has been highlighted in previous quantitative and qualitative research with caregivers (Carlander et al, 2011;Stenberg et al, 2012). Throughout the interviews, most of the caregivers referred to their caregiving experience prior to starting the exercise programme as overwhelming, wherein they struggled to cope and find time for their own self-care.…”
Section: Discussionmentioning
confidence: 93%
“…Research has demonstrated that physical and emotional health may be negatively impacted. Caregivers have described the challenges of caregiving to be overwhelming and unpredictable (Stenberg, Ruland, Olsson, & Ekstedt, 2012) with numerous aspects of their lives being altered (Stenberg et al, 2012). Caregivers have described the challenges of caregiving to be overwhelming and unpredictable (Stenberg, Ruland, Olsson, & Ekstedt, 2012) with numerous aspects of their lives being altered (Stenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations